The Politics of Technical Assistance in Regional Integration Processes: Mesoamerican Insights - Almaguer-Kalixto, Patricia Eugenia (Iberoamerican Journal of Development Studies, 2016)
This paper analyses a regional integration process that includes Belize, Colombia, Costa Rica, Dominican Republic, El Salvador, Honduras, Guatemala, Mexico and Panama. Formally launched in 2001 as the Puebla-Panama Plan (PPP) with a strong commitment to sustainable development and safeguarding the environmental dimension of the regionalisation process, its current version, renamed the Mesoamerican Project (Proyecto Mesoamérica, PM), does not have the same orientation or goals. This paper addresses two questions: a) which stakeholders and discourses shaped the regional integration’s environmental policy process during its different phases? and b) how have the PPP and PM contributed to the environmental governance of the region? The findings suggest that the process has been characterised by strong intervention on the part of supra-national stakeholders that have prioritised liberalisation over the sustainable development agenda for 15 years, weakening regional environmental agencies’ ability to produce warrants to reduce the environmental impacts of regionalisation.
Keywords: regional integration; environmental policy process; Mesoamerican Project; South-South Cooperation; sustainable development